MELACAK PERAN POLITISI PEREMPUAN DI DPRD KOTA YOGYAKARTA Studi Kasus Peran Politisi Perempuan Di DPRD Kota Yogyakarta Periode 2009-2014 - , DERINDA KUSUMA ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Women are social creatures that has its own charm. The presence raises the pros and cons of understanding of their role in society as a woman. Women who choose a gentle nature, sense when compared with men who have a rational nature, strong and mighty. Gave rise to the notion that women can only be number two, eventually only a minority who doubt his ability by men. In social circles, the emergence of the notion that women can only be a sidekick sidekick to her husband, she does not have a high school and the notion of women can only be able to play a role in the domestic sphere. Making women considered one eye, whereas many women in Indonesia, which has the ability and capability in the public realm. It makes women are still discriminated against and the second person. It makes women got up and showed that he was able to par with men. Begin, in Indonesian women who go into politics and into the political parties and run for the legislature. The presence of 30% quota for women are giving the opportunity for women to show its role in the fight for women's representation in the realm of gender in the legislative decision-making of laws, gender-sensitive budgeting and oversight conducted as a member of the legislature. Therefore, researchers interested in conducting research in Yogyakarta City Council in the period 2009-2014 in view of the extent to which the role of women in the third run poltisi function. What are the forms of struggle of women politicians in the DPRD Yogyakarta city in the face of obstacles in carrying out its role.